Economic Crisis and Its Impact:Chemical industry in Thailand - Chuchottaworn, Pailin (ASEAN Journal of Chemical Engineering, 2022)
The economic crisisthat started in Thailand since July 2, 1997 has escalated into a contagious global recession in 1998. ASEAN including Korea were probably among the hardest hit economies under the crisis. [t was generally believed that the crisis was caused by lack of discipline among the private sector and outdated financial infrastructure in view of rapid and accelerated market liberalization. From the chemical industry viewpoint, the industry plays a critical role in propelling industrialization effort in Thailand. The industry, along with steel and cement industries,serves as the three main pillarsfor furtherdevelopments of other downstream manufacturing industries such as auto. electronics, home appliances, etc. Chemical industry in precrisis era used to enjoy a good GDP annualiz!;!d average growth rate of around 20 percent. With an aggressive growth rate for long period. the industry, along with Thai economy, face, peril in the 1997 crisis. The crisis effectively sets-back local demand by 3 years and forces the industry to reexamine its position and strategy for a more stable and sustainable growth in next millennium. The crisisrenders a costly check and balance tools for developing economies in ASEAN to strictly maintaining fine balance and harmony in all facets of developments, industrial,human, legaland moral framework, etc. From various macroeconomic indicies announced recently, Thai economy is on the path of recovery. Local demands along with the export of chemical products have improved in the firsthalf of 1999 and the tendency for the second half is rather promising.